The Impact of Sira Vedha (Phlebotomy) at the Right Elbow Joint in the Treatment of Non-Alcoholic Fatty Liver Disease - A Research Report - Gaurav Sawarkar; Punam Sawarkar (Journal of Pharmacy and Bioallied Sciences)
Non-alcoholic fatty liver disease (NAFLD) affects 9%–53% of the Indian population. No Indian studies have examined Sira Vedha (phlebotomy) for NAFLD, although it has been studied for other conditions. Sushruta recommended Sira Vedha at the right elbow joint for liver diseases, but clinical evidence for its efficacy in NAFLD is lacking. This clinical trial aimed to generate evidence for Sira Vedha in NAFLD patients. One hundred eleven patients with Grade I/II NAFLD were randomly assigned to either a control group (diet and exercise) or an intervention group (Sira Vedha, diet, and exercise). Blood samples were collected for lipid profile and liver function tests before and after treatment. Results showed significant improvements in SGOT, SGPT, cholesterol, HDL, and triglyceride levels in the intervention group compared to the control group, supporting the efficacy of Sira Vedha in NAFLD treatment. This study highlights the need for clinical evidence to confirm traditional Ayurvedic practices.